Modified Transposition Using TDEA Encryption for FishCoral-PRSA Management System - Balilo Jr., Benedicto B.; Dioneda Sr., Ronnel R.; Byun, YungCheol (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2020)
Purpose   – The purpose of this study is to developed an encryption technique with a modified transposition technique using TDEA for FishCoral-PRSA Management Information System.  A project component of Participatory Resource and Socio-Economic Assessment (PRSA) was implemented under the Fisheries, Coastal Resources and Livelihood (FishCORAL) project of the Bureau of Fisheries and Aquatic Resource of Department of Agriculture (DA-BFAR).   Method – The developed encryption algorithm followed the concept of a rational unified process.  The characteristics of the existing transposition and 3DES algorithms were analyzed including the plaintext parameters, entropy, block size, and others.  The algorithm was developed in PHP language and simulated through login authentication to evaluate the ciphertext and speed performance. Results –   Businesses and organizations are providing security mechanisms to prevent security breaches or attacks to the system which could result in data loss and disruption of service with cost to the organization.  The results of this study aimed to introduce a new encryption algorithm by merging the features of the transposition technique and characteristics of the 3DES algorithm placing several parameters (as salt) in the entropy.  Thus, it reveals that the results in-placed with reference code generated a complex ciphertext—a challenge to consider in the future. Conclusion – The developed algorithm makes use of modified transposition in 2-layered order and 3DES algorithm to secure the login account.  The encryption and decryption times were 0.15044 ms and 0.78666 ms, respectively.  The encryption sequence order follows the row read-off order while the decryption implemented a column read-off sequence order based on defined column order.  The transposition sequencing added ingredients to the encryption process and generated a complex symbol. Recommendations – There is no detailed approach on how to prevent an attack and avoid security breaches in the system.  A complex or simple idea that led to the introduction of a new encryption algorithm provides an opportunity for login authentication, protection for file content, and securing transactions and messages. Research Implications – The developed algorithm is significant to the FishCoral-PRSA project as this offers exclusivity to the system features especially user login authentication.  Furthermore, this offers challenges and opportunities, especially for cybersecurity novice.